Analisis dan Perancangan Sistem Informasi Kesehatan Sebaran Penyakit Berbasis WEB-GIS - Jeremi Yohanes Mocodompis; Frederik Samuel Papilaya (STMIK Budi Darma, 2023)
Manado City is the capital of North Sulawesi province. According to the Central Statistics Agency, in 2019 there were 4,646 cases of infectious diseases reported in the city. This poses a health problem as it can threaten the well-being of the population. Currently, information regarding the spread of infectious diseases in Manado is relatively limited, leading to a lack of awareness among the community about the presence of contagious diseases in their surroundings. Given this issue, an information system is needed to map the distribution of diseases, particularly infectious diseases, to ensure that information about disease spread can be effectively communicated to the public. Geographic Information System (GIS) provide significant benefits in addressing the issue of disease spread. GIS allows for clear and detailed visual mapping of disease distribution. Disease case data can be mapped onto an interactive map, indicating their locations and geographical distribution. The analysis and design of a web-based GIS health information system is an effort to integrate geographic information systems and health data through a web platform. The research methods employed include interviews, observations, and literature studies. The system development method utilizes the Waterfall SDLC (Systems Development Life Cycle) and Laravel 8 as the programming framework. The research findings indicate that the web-based GIS health information system provides an effective and efficient solution in managing and utilizing geographic information and health data to map the spread of diseases in Manado City, while also benefiting the dissemination of information to the community